Patrol Music as an Educational Medium for Exploring History, Cultural Values, and Musical Functions in Primary Schools - Proborini, Chandra Ayu; Mayangsari, Marrisa Aulia; Muhammad Ahsin Maulana, Muhammad Ahsin Maulana Muhammad Ahsin Maulana (Universitas Trunojoyo Madura, 2025)
Traditional arts hold a vital role in preserving cultural identity and fostering character education in early schooling. Patrol music, a community-based percussive ensemble developed in local traditions, offers rich historical, cultural, and educational values that remain underutilized in formal education. This study investigates the potential of patrol music as a pedagogical medium in elementary school education. This study employs a qualitative approach using the literature review method. Academic journals, books, and institutional reports were analyzed to examine the historical development, cultural significance, and pedagogical relevance of patrol music within the framework of contextual and thematic learning. The findings reveal that patrol music does not only serve as an engaging tool to contextualize subjects (e.g. Social Studies, Civic Education, and Arts), but it is also as a medium to cultivate students’ social-emotional skills, including cooperation, empathy, and cultural pride. Integrating it into the school curriculum could align with character education and local wisdom-based learning emphasized in curriculum policy in Indonesia. To maximize the educational potential of patrol music, some strategic actions are recommended, such as administering teacher training, developing local-based learning resources, and encouraging collaboration with cultural communities. These steps are critical in revitalizing traditional arts education and reinforcing cultural resilience among younger generations.